2021
DOI: 10.21203/rs.3.rs-1052733/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drought-induced Forest Dieback Increases Taxonomic and Functional Diversity But Not Phylogenetic Diversity of Saproxylic Beetles at Both Local and Landscape Scales

Abstract: Context: Forest ecosystems worldwide are facing increasing drought-induced dieback, causing mortality patches across the landscape at multiple scales. This increases the supply of biological legacies and differentially affects forest insect communities.Objectives: We analysed the relative effects of local- and landscape-level dieback on local saproxylic beetle assemblages. We assessed how classic concepts in spatial ecology (e.g. habitat-amount and habitat-patch hypotheses) are involved in relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…On the one hand, it has been shown that the functional diversity of saproxylic beetles is driven mainly on the regional level, whereas local diversity simply mirrors those patterns (Hagge et al, 2019). In that case, large‐scale forest characteristics could be more relevant, as observed for example in naturally disturbed forests (Cours et al, 2021). On the other hand, the importance of variables directly characterizing the beetle species occurrences and their relationship to specific microhabitats has also been emphasized (Dolek et al, 2009; Micó et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it has been shown that the functional diversity of saproxylic beetles is driven mainly on the regional level, whereas local diversity simply mirrors those patterns (Hagge et al, 2019). In that case, large‐scale forest characteristics could be more relevant, as observed for example in naturally disturbed forests (Cours et al, 2021). On the other hand, the importance of variables directly characterizing the beetle species occurrences and their relationship to specific microhabitats has also been emphasized (Dolek et al, 2009; Micó et al, 2020).…”
Section: Discussionmentioning
confidence: 99%